Achieving optimal physical fitness and health safety in 19-21 year old judo athletes - Natalia Boychenko; Wladyslaw Jagiello (Pedagogy of Health)
Background and Study Aim. Physical fitness is crucial for the success of athletes in competitive sports. However, often the impact of physical exertion on athlete health is overlooked. The study aims to investigate the relationship between the level of physical fitness and competitive performance of judokas aged 19-21.